Dysregulation of SIRT-1 Signaling in Multiple Sclerosis and Neuroimmune Disorders: A Systematic Review of SIRTUIN Activators as Potential Immunomodulators and their Influences on other Dysfunctions - Sharma, Nidhi; Shandilya, Ambika; Kumar, Nitish; Mehan, Sidharth (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Immune dysregulation, neuronal inflammation, and oligodendrocyte degradation are key causes for autoimmune disorders like multiple sclerosis (MS) and various other immune dysregulated neurodegenerative complications responsible for CNS-mediated immune responses. Sirtuin (SIRT-1) is a nicotinamide adenosine dinucleotide (NAD)-dependent transcriptional protein that deacetylases and removes acetyl groups from its transcription factors like P53, FOXO, NF-b, PGC-1α. SIRT-1 mediates a wide range of physiological functions, including gene transcription, metabolism, neuronal apoptosis, and glucose production. SIRT-1 dysregulation targets transcription factors, and other molecular alterations such as gene expression modification influence neuronal plasticity, inhibit Th17 cells, and interleukin-1β can aggravate brain diseases. Preclinical and clinical findings show that the upregulation of SIRT-1 reduces autoimmunity, neurodegeneration, and neuroexcitation. Even though drugs are being developed for symptomatic therapies in clinical trials, there are particular pharmacological implications for improving post-operative conditions in neurodegenerative patients where intensive care is required. Understanding the SIRT-1 signaling and identifying immune-mediated neuron deterioration can detect major therapeutic interventions that could prevent neuro complications. Thus, in the current review, we have addressed the manifestations of disease by the downregulation of SIRT-1 that could potentially cause MS and other neurodegenerative disorders and provided data on existing available and effective drug therapies and disease management strategies.
Keywords: inflammation